A Novel Noninvasive Device to Assess Sympathetic Nervous System Function in Patients With Heart Failure. Issue 5 (September 2015) - Parry, Monica; Nielson, Chantelle A.; Muckle, Fiona; O'Keefe-McCarthy, Sheila; van Lien, Rene; Meijer, Jan H.
<x xml:space="preserve">Abstract</x> Background Heart failure is a complex syndrome associated with sympathetic nervous system and renin–angiotensin–aldosterone system hyperactivity. Sympathoinhibition and downregulation of sympathetic activity using medications and exercise training improve outcomes in patients with heart failure. Impedance cardiography provides data on hemodynamic and autonomic function that may assist with safe medication, exercise monitoring, and titration. Purpose The purpose of this pilot study was to evaluate the sensitivity of the Vrije Universiteit Ambulatory Monitoring System (VU-AMS) version 5fs to detect hemodynamic and sympathetic nervous system changes associated with postural shift in persons with heart failure with reduced ejection fraction. Methods In this descriptive study, participants (N = 28) were recruited from an outpatient device clinic at a tertiary care hospital in Ontario, Canada. They completed a sit-to-stand posture protocol wearing an ambulatory blood pressure (ABP) and a noninvasive VU-AMS version 5fs impedance cardiography system. Results Most (n = 18, 64%) participants were eliminated from the final analyses in this sample because of difficulty in Q-onset and B-point identification in peculiar electrocardiogram and impedance cardiogram waveforms. The remaining participants (n = 10) had a mean age of 69 years (SD = 10 years) and responses to a sit-to-stand posture protocol that included a 5% increase in heart rate (p = .001), an 18% decrease in stroke volume (p = .01), and an 8% decrease in left ventricular ejection time (p = .01). Participants had an increased preejection period (11%, p = .01), a drop in cardiac output of 13% (p = .02), and a reduced mean arterial pressure of approximately 4% (p = .09) with standing. Discussion Although the VU-AMS version 5fs system detected anticipated hemodynamic and sympathetic nervous system changes to postural shift in participants (n = 10), the elimination of 64% (n = 18) of the sample because of scoring difficulties limits the use of this impedance cardiography device using standard scoring algorithms in persons with heart failure with reduced ejection fraction.